DYNAMIC SIMULATION AND TEST ANALYSIS OF SPACE TRUSS AND LOAD STRUCTURE - Luo, Haitao; Wang, Peng; Wu, Tingke; Wang, Haonan (International Journal of Engineering Technologies and Management Research, 2018)
The dynamic characteristics of aerospace products play a decisive role in environmental adaptability of products, because aerospace products are subjected to vibration environment during launching process. This paper describes the design of a space truss and the load structure, in order to get the dynamic characteristics, finite element modal analysis and modal test is done on the structural model, through correlation analysis to determine the degree of conformity of the finite element model with the experimental model. It is determined that the finite element mode of truss and load structure is similar to the test mode, the finite element model is acceptable; The dynamic simulation of the structure is carried out by the qualified finite element model, and the dynamic simulation results are verified by the vibration test; The method for obtaining the dynamic characteristics of aerospace products and the way of dynamic simulation for launching process is of great reference value for the design of aerospace products.